EFEK PEMBINGKAIAN DAN TINGKAT KEPEDULIAN TERHADAP PIHAK LAIN PADA HARGA TRANSFER AKHIR ESTIMASIAN NEGOSIASIAN - ARIEF, SANDY ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Transfer price negotiations are important to managers as they influence both their own and other divisional profits. These transfer prices are affected by both economic factors (market prices) and behavioral factors including fairness on judgments about negotiated transfer prices. In the current study, I examine whether the impact of accounting information on managers’ transfer price expectations are affected by the way accounting information is framed (either as potential gains or potential losses) and the managers’ perception of the other negotiation partners’ objective (whether their partner’s objective involves high or low concern-for-others). These expectations are important as they directly affect the costs and outcomes of negotiations. A controlled laboratory experiment was conducted to test the proposed hypotheses, using a 2 x 2 x 2 between-subjects design. The participants of experiment were 216 undergraduate accounting students from Faculty of Economics and Business, Soegijapranata Catholic University, Semarang. The results of this study that compared to a gain frame, a loss frame exacerbates managers’ self serving bias and increases the transfer price expectation gap between buyers and sellers. Further, I found that the negotiation partner’s objective had a significant impact on sellers’ transfer price judgments. This finding is particularly interesting as sellers in my experiment had relatively strong bargaining power but these sellers did not exploit their bargaining power by demanding high transfer prices regardless of their partner’s level of concern-for-others.